Good School Toolkit-Secondary Schools to prevent violence against students: protocol for a pilot cluster randomised controlled trial - Devries, Karen; Tanton, Clare; Knight, Louise; Nakuti, Janet; Nanyunja, Barbrah; Laruni, Yvonne; Amollo, Mathew; Apota, John; Opobo, Timothy; Pearlman, Jodie; Allen, Elizabeth; Bonell, Chris; et al. (British Medical Journal Publishing Group, 2024)
IntroductionNo whole-school interventions which seek to reduce physical, sexual and emotional violence from peers, intimate partners and teachers have been trialled with adolescents. Here, we report a protocol for a pilot trial of the Good School Toolkit-Secondary Schools intervention, to be tested in Ugandan secondary schools. Our main objectives are to (1) refine the intervention, (2) to understand feasibility of delivery of the intervention and (3) to explore design parameters for a subsequent phase III trial.Methods and analysisWe will conduct a pilot cluster randomised controlled trial, with two arms and parallel assignment. Eight schools will be randomly selected from a stratified list of all eligible schools in Kampala and Wakiso Districts. We will conduct a baseline survey and endline survey 18 months after the baseline, with 960 adolescents and 200 teachers. Qualitative data and mixed methods process data collection will be conducted throughout the intervention. Proportion of staff and students reporting acceptability, understanding and implementing with fidelity will be tabulated at endline for intervention schools. Proportions of schools consenting to participation, randomisation and proportions of schools and individual participants completing the baseline and endline surveys will be described in a Consolidated Standards of Reporting Trials diagram.Ethics and disseminationThe ethical requirements of our project are complex. Full approvals have been received from the Mildmay Ethics Committee (0407-2019), the Uganda National Council for Science and Technology (SS 6020) and the London School of Hygiene & Tropical Medicine (16212). Results of this study will be published in peer-reviewed academic journals, and shared with public bodies, policy makers, study participants and the general public in Uganda.Trial registration numberPACTR202009826515511.
Keywords: School Toolkit; Secondary Schools; violence